A randomised controlled trial of azithromycin therapy in bronchiolitis obliterans syndrome (BOS) post lung transplantation. Issue 5 (24th February 2015) - Corris, Paul A; Ryan, Victoria A; Small, Therese; Lordan, James; Fisher, Andrew J; Meachery, Gerard; Johnson, Gail; Ward, Chris
Abstract : Background: We conducted a placebo-controlled trial of azithromycin therapy in bronchiolitis obliterans syndrome (BOS) post lung transplantation. Methods: We compared azithromycin (250 mg alternate days, 12 weeks) with placebo. Primary outcome was FEV1 change at 12 weeks. Results: 48 patients were randomised; (25 azithromycin, 23 placebo). It was established, post randomisation that two did not have BOS. 46 patients were analysed as intention to treat (ITT) with 33 'Completers'. ITT analysis included placebo patients treated with open-label azithromycin after study withdrawal. Outcome: The ITT analysis (n=46, 177 observations) estimated mean difference in FEV1 between treatments (azithromycin minus placebo) was 0.035 L, with a 95% CI of −0.112 L to 0.182 L (p=0.6). Five withdrawals, who were identified at the end of the study as having been randomised to placebo (four with rapid loss in FEV1, one withdrawn consent) had received rescue open-label azithromycin, with improvement in subsequent FEV1 at 12 weeks. Study Completers showed an estimated mean difference in FEV1 between treatment groups (azithromycin minus placebo) of 0.278 L, with 95% CI for the mean difference: 0.170 L to 0.386 L (p=<0.001). Nine of 23 ITT patients in the azithromycin group had ≥10% gain in FEV1 from baseline. No patients in the placebo group had ≥10% gain in FEV1 from baseline while on placebo (p=0.002). Seven serious adverse events, three azithromycin, four in the placebo group, were deemed unrelated to study medication. Conclusions: Azithromycin therapy improves FEV1 in patients with BOS and appears superior to placebo. This study strengthens evidence for clinical practice of initiating azithromycin therapy in BOS. Trial registration number: EU-CTR, 2006-000485-36/GB.